2016
DOI: 10.1108/jes-09-2014-0166
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external determinants of banks’ profitability

Abstract: Purpose – The purpose of this paper is to analyze the profitability of 27 universal banks in Portugal over the period from 2002 to 2011. Design/methodology/approach – The paper conducts ordinary least squares estimations with fixed effects using three measures of profitability: the return on average assets, the return on average equity and the net interest margin. Several independent variables were included concerning both bank-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
141
4
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 93 publications
(167 citation statements)
references
References 16 publications
17
141
4
5
Order By: Relevance
“…This result is consistent with Garcia and Guerreiro (2016) and Rashid and Jabeen (2016) who reported that the real GDP growth has a negative impact on profitability. This result is consistent with Garcia and Guerreiro (2016) and Rashid and Jabeen (2016) who reported that the real GDP growth has a negative impact on profitability.…”
Section: Macroeconomic Determinants Of Indian Banks' Profitabilitysupporting
confidence: 92%
See 4 more Smart Citations
“…This result is consistent with Garcia and Guerreiro (2016) and Rashid and Jabeen (2016) who reported that the real GDP growth has a negative impact on profitability. This result is consistent with Garcia and Guerreiro (2016) and Rashid and Jabeen (2016) who reported that the real GDP growth has a negative impact on profitability.…”
Section: Macroeconomic Determinants Of Indian Banks' Profitabilitysupporting
confidence: 92%
“…Following prior studies (e.g., Athanasoglou et al, 2008;Garcia & Guerreiro, 2016;Naeem et al, 2017;Pathneja, 2016;A. Following prior studies (e.g., Athanasoglou et al, 2008;Garcia & Guerreiro, 2016;Naeem et al, 2017;Pathneja, 2016;A.…”
Section: Dependent Variablesmentioning
confidence: 91%
See 3 more Smart Citations